Effects of climate change on the distribution of indigenous species in oceanic islands (Azores) - Ferreira, Maria T. (2018)
Oceanic islands host a high proportion of the world’s endemic species. Many such species are at risk of extinction owing to habitat degradation and loss, biological invasions and other threats, but little is known about the effects of climate change on island native biodiversity. The Azorean archipelago provides a unique opportunity to study species-climatechange relationships. We used ensemble forecasting to evaluate the current and future distribution of well-studied endemic and native bryophytes (19 species), endemic vascular plants (59 species) and endemic arthropods (128 species), for two of the largest Azorean Islands, Terceira and São Miguel. Using a Regional Climate Model (CIELO), and assuming the extreme scenario RCP8.5, we examined changes in the potential distributions of the species and possible loss of climate space for them. Models projected that 23 species (11 %) could lose all adequate climate on either one or both islands. Five additional species were projected to lose ≥90 % of climate space. In total, 90 % of the species were projected to lose climate space: 79 % of bryophytes, 93 % of vascular plants and 91 % of arthropods. We also found for vascular plants and arthropods a tendency for upward shift in altitude in their suitable climate space, while for bryophytes the shift was towards the coastal areas. Our results have profound implications for future conservation priorities on islands, such as for the redrawing of conservation borders of current protected areas.